2005
DOI: 10.1016/j.cognition.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Attention capacity and task difficulty in visual search

Abstract: When a visual search task is very difficult (as when a small feature difference defines the target), even detection of a unique element may be substantially slowed by increases in display set size. This has been attributed to the influence of attentional capacity limits. We examined the influence of attentional capacity limits on three kinds of search task: difficult feature search (with a subtle featural difference), difficult conjunction search, and spatial-configuration search. In all 3 tasks, each trial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
113
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(119 citation statements)
references
References 23 publications
6
113
0
Order By: Relevance
“…Second, and perhaps more surprising, the L decoys produced stronger localized attentional interference with O targets than did the C decoys. Both of these findings might be attributable to the type of perceptual processing necessary to distinguish a T from an L and an O from a C. As others have noted, the T-L discrimination involves distinguishing the relative spatial locations of a common set of features (Huang & Pashler, 2005;Wolfe, 1998), whereas the O-C discrimination involves identifying the presence or absence of a feature (e.g., a gap or closure; Treisman & Souther, 1985). The data suggest that the spatial arrangement discrimination involved in distinguishing a T from an L may be more resource intensive (Huang & Pashler, 2005) than is the feature detection task required to discriminate an O from a C. This may leave the O-shaped targets less susceptible to localized attentional interference than are the T-shaped target stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…Second, and perhaps more surprising, the L decoys produced stronger localized attentional interference with O targets than did the C decoys. Both of these findings might be attributable to the type of perceptual processing necessary to distinguish a T from an L and an O from a C. As others have noted, the T-L discrimination involves distinguishing the relative spatial locations of a common set of features (Huang & Pashler, 2005;Wolfe, 1998), whereas the O-C discrimination involves identifying the presence or absence of a feature (e.g., a gap or closure; Treisman & Souther, 1985). The data suggest that the spatial arrangement discrimination involved in distinguishing a T from an L may be more resource intensive (Huang & Pashler, 2005) than is the feature detection task required to discriminate an O from a C. This may leave the O-shaped targets less susceptible to localized attentional interference than are the T-shaped target stimuli.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, several studies have indicated that capacity limitations do not depend on difficulty. Huang and Pashler (2005), for example, demonstrated a dissociation between difficulty and capacity using the simultaneous-sequential paradigm. They found that out of three difficult visual search tasks (feature, spatial conjunction, and feature conjunction), one showed evidence of being limited capacity (spatial conjunction), and the other two did not.…”
Section: Task Difficultymentioning
confidence: 99%
“…Such models have been successful in predicting performance for tasks that rely on the perception of simple visual features, such as luminance, orientation, and size (see, e.g., Bonnel, Stein, & Bertucci, 1992;Davis, Shikano, Peterson, & Michel, 2003;Palmer, Verghese, & Pavel, 2000;Scharff, Palmer, & Moore, 2011). Simple-feature tasks can be made difficult and slow by adjusting such stimulus parameters as target-distractor similarity, but still they have unlimited capacity (Huang & Pashler, 2005).…”
Section: Capacitymentioning
confidence: 99%
“…Visual search tasks have become one of the most widely used tool in the study of selective attention (Huang & Pashler, 2005). They involve presenting a target, hidden amongst non-target elements, and asking the participant to locate the target.…”
Section: Visual Searchmentioning
confidence: 99%